Anonymous feedback in e-learning systems - Dreher, Heinz (Association for the Advancement of Computing in Education, 2005)
Prima facie it is accepted that anonymity is an important feature of E-Learning systems. It is easy to implement. But this simplicity belies its more serious implications, especially regarding the worth which can be attached to results derived from the interpretation and analysis of anonymously collected data. We review a sample of E-Learning implementation cases from the point of view of anonymously collected data for evaluation of educational quality. A reiteration of an earlier analysis of levels of anonymity then leads us to argue that the use of our Anonymity levels/Purpose/Worth matrix will benefit practitioners and researchers in the E-Learning field.